PEMIDANAAN ANAK MENURUT HUKUM ISLAM DAN HUKUM PIDANA INDONESIA - Adam Sani (Jurnal Public Policy, 2015)
Children is that of Allah swt which exists to the world is on the nothing but (pure children as the youth is the successors to achieve struggles and human resources for the development of nasional. children need guidance and attention specifically, Especially their parents and the government to achieve the development of physical , mental and spiritual maximally .The rule of law against children a criminal offense in Indonesia arranged in act no. 3 year 1997 on court children later improved by the law no. 11 2012 about the justice system children .Hence , if the child a criminal offense therefore his is to be processed legally based on the bill. Law no. 11 2012 about judicial systems children prefer diversi in the form of restorative justice in terms of handle matter children proven to commit crimes. According to islamic law , children committing a commit crimes.Keyword: children,  islamic law, crimes law, of Indonesia